Congenital Falciparum Malaria with Chloroquine Resistance Type ll - Dianto Dianto; T. H. Rampengan (Paediatrica Indonesiana, 1989)
A case of congenial falciparum malaria has been reported. The diagnosis was based Â·on history of illness, clinical manifestations, age of the child and presence of the ring form falciparum malaria in the peripheral blood films. Treatment with chloroquine showed resistance type II, though treatment with quinine was successful. In malaria endemic areas, although rare, one must be aware of the possibility of congenital malaria.